Cytoreductive nephrectomy: past, present and future. Issue 3 (March 2014) - Galazi, Myria; Rodriguez-Vida, Alejo; Josephides, Eleni; Chau, Noan-Minh; Chowdhury, Simon
<x xml:space="preserve">Abstract</x> Cytoreductive nephrectomy (CN) is an integral part of the treatment of patients with metastatic renal cell carcinoma. Improved survival has been shown with CN and IFN-α. The introduction of targeted therapy for metastatic renal cell carcinoma has raised important questions regarding the role of CN. The majority of patients who were enrolled in the Phase III studies of targeted therapies had undergone prior nephrectomy. Thus, the benefit of these agents has largely been demonstrated in a nephrectomized population. CARMENA and SURTIME, important Phase III studies examining the role and timing of CN, are ongoing. Until new evidence is available, CN is a reasonable approach in selected patients with a resectable primary tumor and good performance status.